2022
DOI: 10.1039/d2tc02104h
|View full text |Cite|
|
Sign up to set email alerts
|

Reliable high work-function molybdenum dioxide synthesis via template-effect-utilizing atomic layer deposition for next-generation electrode applications

Abstract: MoO2, a conductive metal oxide, has attracted considerable attention as an electrode material in metal–insulator–metal (MIM) capacitors owing to its crystallinity and high work function. However, because MoO2 is a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…24 Kim et al suggested another approach for obtaining ALD MoO 2 films using the TiN substrate-induced template effect. 25 ALD MoO x films were grown on TiN and SiO 2 substrates using Mo(CO) 6 and O 3 , followed by post-deposition annealing (PDA) at 600 °C. On the TiN substrate, the rutile TiO 2 phase formed at the MoO x − TiN interface induced the formation of monoclinic MoO 2 via the template effect of the substrate.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Kim et al suggested another approach for obtaining ALD MoO 2 films using the TiN substrate-induced template effect. 25 ALD MoO x films were grown on TiN and SiO 2 substrates using Mo(CO) 6 and O 3 , followed by post-deposition annealing (PDA) at 600 °C. On the TiN substrate, the rutile TiO 2 phase formed at the MoO x − TiN interface induced the formation of monoclinic MoO 2 via the template effect of the substrate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was found that monoclinic MoO 2 was formed after PDA in H 2 atmosphere, whereas the MoO 3 phase was achieved after PDA in O 2 atmosphere . Kim et al suggested another approach for obtaining ALD MoO 2 films using the TiN substrate-induced template effect . ALD MoO x films were grown on TiN and SiO 2 substrates using Mo­(CO) 6 and O 3 , followed by post-deposition annealing (PDA) at 600 °C.…”
Section: Introductionmentioning
confidence: 99%